Engineering management of gas turbine power plant co2 for microalgae biofuel production - Mathew, Domoyi; Pilidis, Pericles; Di Lorenzo, Giuseppina (Cranfield University Press, 2013)
Fossil fuel accounts for over 80% of the world`s primary energy, particularly in areas of transportation, manufacturing and domestic heating. However, depletion of fossil reserves, frequent threats to the security of fossil fuel supply, coupled with concerns over emissions of greenhouse gases associated with fossil fuel use has motivated research towards developing renewable and sustainable sources for energy fuels. Consequently, the use of microalgae culture to convert CO2 from power plants flue gases into biomass that are readily converted into biofuel offers a window of opportunities to enhance, compliment or replace fossil- fuel-use. Interest in the use of microalgae biomass for biofuel production is high as it affords the potential for power plant CO2 sequestration – (1kg of dry algae biomass uses about 1.83kg CO2). Similarly, its capacity to utilise nutrients from a variety of wastewater, sets it apart from other biomass resources. These outlined benefits all emphasis the need for extended R&D efforts to advance commercial microalgae biofuel production. The paper is aimed at investigating the environmental performance of the microalgae biofuel production process using LCA.
Keywords: Life Cycle Assessment (LCA).; Biofuels; Microalgae biomass